Advances in Critical Care Nursing: Evidence-Based Practices, Clinical Decision-Making, and Quality Improvement - Almutairi, Tefla Munif; Alshahrani, Alanoud Saeed; Alhuraysi, Maha Mohammed Asaad; Alahmari, Heton Mohammed Ali; Albishi, Munirah Amer Mousa; Hazazi, Ahlam Ahmad; Huraysi, Huda Salman Al; Alwalah, Salem Qublan; Alnujaym, Abdulrahman Mubarak; Ghazwani, Norah Ali jaber (Journal of Posthumanism, 2024)
Critical care nursing has evolved into a highly specialized discipline that integrates advanced clinical judgment, rapid decision-making, and evidence-based interventions to improve outcomes for critically ill patients. This review synthesizes contemporary evidence (2016–2025) on the role of critical care nurses, focusing on advanced practices, clinical reasoning models, and quality improvement strategies that optimize patient safety and survival. Key domains analyzed include hemodynamic monitoring, early recognition of deterioration, ventilator management, infection prevention bundles, and multidisciplinary communication frameworks. The review further examines how cognitive load, clinical heuristics, and technological integration influence nurses’ decision-making accuracy in high-acuity settings. A conceptual model illustrating pathways linking nursing competencies to patient outcomes is presented. Evidence shows that advanced critical care nursing practices significantly reduce mortality, improve early intervention rates, and strengthen compliance with safety standards. The article concludes with recommendations for enhancing training, adopting digital decision-support tools, and strengthening quality improvement programs in intensive care units.